Attenuated PINK1 autophosphorylation play neuroprotective and anti-seizure roles in neonatal hypoxia - Yi Yuan; Xiaoqian Wang; Yaru Cui; Hua Zhou; Wenna Li; Qian Teng; Hongjin Wang; Bohan Sun; Qiaoyun Wang; Hongliu Sun; Jianhua Tang (Scientific Reports)
Abstract This study investigated the roles and mechanisms of PINK1 activity in neonatal hypoxia-induced seizures with shRNA intervention targeting translocase outer mitochondrial membrane 7 (TOM7), the positive regulator of PINK1 autophosphorylation, or overlapping with the m-AAA protease 1 homolog (OMA1), the negative regulator of PINK1 autophosphorylation. Studies have suggested that in hypoxia-induced neonatal seizures, the phosphorylation level of PINK1 is significantly increased and the mitophagic pathway is activated, accompanied by neuronal damage and learning-memory deficits. Inhibiting PINK1 phosphorylation by reducing TOM7 expression alleviated mitophagy, mitochondrial oxidative stress, neuronal damage and seizures. In contrast, the inhibition of OMA1 expression resulted in a further increase in PINK1 phosphorylation and aggravated hypoxia-induced seizures and neuronal injury. This study implicated PINK1 activity in neonatal hypoxia and suggest that attenuated PINK1 autophosphorylation may have neuroprotective and anti-seizure effects in neonatal hypoxia.